DNA Isolation on Captive Sumatran Elephant in Elephant Training Center, Way Kambas National Park: A First Step towards Its ID Card - Elly L. Rustiati; Priyambodo Priyambodo; Siti Asiyah; Dedi Candra; Diah E. Anggraini; Elizabeth D. Krismuniarti; Eko Agus Srihanto; Liza Angeliya; Nuning Nurcahyani; Enny Saswiyanti (International Journal of Tropical Veterinary and Biomedical Research, 2018)
Elephant Training Center (ETC) Way Kambas National Park (WKNP) was built to support human-elephant mitigation conflict. The small population of captive sumatran elephant in ETC WKNP need a comprehensive strategy in order to maintain the genetic variation of each individual and avoid inbreeding drive. Currently, genetic studies have opened new field studies in ecology, included conservation ecology. Patterns in variation of population has been investigated by molecular method supporting species conservation effort. The captive sumatran elephant’s ID Card is a necessary in database building, which included morphology, health status, and genetic profile. Genetic profile in each ID Card was filled by cytogenetic and molecular profile for RADP result, that initiated with DNA isolation. The DNA sources collected by blood sampling protocol described by Asiyah et al. (2016) from captive sumatran elephant in ETC, WKNP, and be carried to laboratory in cold condition. The DNA sources stored at 4oC and isolated following commercial protocol. The result of DNA isolation stored at -20oC until amplification analysis. DNA isolation was successfully done, for further individual genetic ID building.